2018
DOI: 10.1111/jocd.12678
|View full text |Cite
|
Sign up to set email alerts
|

Pigmented transverse nasal band: A distinct presentation

Abstract: Pigmented transverse nasal band (PTNB) is an interesting morphological entity mainly of cosmetic concern. It is believed to be related to a defect in the development of the nasal cartilages and bones from childhood to adolescence. Some patients may have genetic predisposition. It is asymptomatic in nature and may be associated with certain dermatological conditions such as seborrheic diathesis, dermatosis papulosa nigra, ichthyosis, atopic dermatitis, acne vulgaris, psoriasis, and seborrheic melanosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…1,2 In addition, Wimmershoff et al reported two cases that presented at birth. 6 There might be a genetic 7 and racial predilection 8 in Caucasians.…”
Section: It Occurs Sporadically In the General Population A Familial Basis Has Been Reported By Anderson Which Is Supported By Anmentioning
confidence: 99%
See 4 more Smart Citations
“…1,2 In addition, Wimmershoff et al reported two cases that presented at birth. 6 There might be a genetic 7 and racial predilection 8 in Caucasians.…”
Section: It Occurs Sporadically In the General Population A Familial Basis Has Been Reported By Anderson Which Is Supported By Anmentioning
confidence: 99%
“…For example, in case of a larger lower lateral nasal cartilage, the lesion may shift a few millimeters upwards. 4,7 Anderson suggested a genetic predisposition, due to the inheritance of a single dominant gene. 2 An embryological origin has also been proposed by Shelley et al, as the nose forms at six weeks of gestation by fusion of medial nasal process with frontonasal process.…”
Section: Etiopathogenesismentioning
confidence: 99%
See 3 more Smart Citations